A rare case report of an solitary neurofibroma in postcricoid region of hypopharynx - Li, Dongjie (Medicine (Baltimore), 2021)
RATIONALE: Postcricoid neurofibroma is an extremely rare hypopharynx tumor that can be challenging in both diagnosis and treatment. This case sheds light on the possibility of treatment with transoral microsurgery before pursuing open cervical incisions. PATIENT CONCERNS: : A 43-year-old man presented with a four months history of a persistent foreign body sensation and mild dysphagia. Indirect and direct laryngoscopy at admission revealed a round and smooth submucosal mass in the postcricoid region. DIAGNOSIS: A laryngeal enhanced computed tomography and laryngoscopy suggested that the tumor located in hypopharynx, with clear boundary and slightly strengthened edge. A supporting laryngoscopy surgery was performed under general anesthesia and a biopsy confirmed solitary neurofibroma of the postcricoid region. INTERVENTIONS: The tumor was successfully resected en bloc transorally through supporting laryngoscope, and obviated the need for open cervical surgery and tracheostomy. OUTCOMES: The patient recovered well without any intraoperative or postoperative complication and was discharged from hospital 2 days after surgery. There was no recurrence after 6 months follow-up. LESSONS: Postcricoid neurofibroma is an extremely rare hypopharynx tumor that can be diagnostically challenging. To the best of our knowledge, this is the first case reported of solitary neurofibroma originating from the postcricoid region of the hypopharynx and was surgically removed with transoral surgery through supporting laryngoscope.